Gastric proton pump with two occluded K+ engineered with sodium pump-mimetic mutations - Kazuhiro Abe (Nature Portfolio, 2021)
The gastric H+,K+-ATPase is a proton pump that creates the acidic environment of the stomach lumen, maintaining high proton gradient across the gastric mucosa cell membrane. Here, structural analysis of rationally designed H+,K+-ATPase mutants provides insight into this and other P-type ATPases cation binding stoichiometry and mechanisms.